Open Problem Based Learning (OPBL) Learning Model on Student Learning Outcomes in Operating System Lessons At Vocational High School: Model Pembelajaran Open Problem Based Learning (OPBL) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Sistem Operasi di SMK - Rifkah Umami Indah Lestari; Rahmania Sri Untari (Universitas Muhammadiyah Sidoarjo, 2021)
Online learning during the pandemic has an impact on student learning scores decreasing. The purpose of this study is to improve the results of student learning scores. The research model used by the researcher is experimental quantitative. The results showed that there was an influence between the pretest using the problem based learning model and the posttest using the open problem based learning model that occurred in the XMM4 class, where this class would be given a treatment before and after applying the Open Problem Based Learning learning model. The teacher will give a problem and students will solve the problem based on their understanding of the analysis, where students are given the freedom to convey their respective arguments through questions related to computer operating system subjects. With the increasing value of learning, Open Problem Based Learning is an appropriate learning model for teachers of SMK Yapalis Krian.